Optimization of water flow on Regency Municipality Waterworks-network of Jonggat Central Lombok Regency using Ford Fulkerson Algorithm and Dinic Algorithm - Lilis Sriwahyuni; Marwan Marwan; Zata Yumni Awanis (University of Mataram, 2023)
Clean water is essential for humans which must be fulfilled for humans survival. The population in Jonggat, Central Lombok, increases from year to year which causes the using of clean water get an increase too. The necessity of rising clean water is not in line with the availability of water in nature, therefore the PDAM (Regency Municipality Waterworks) manages existing water resource. Then, it will be distributed to consumers. The purpose of this research is to determine the optimal solution in the distribution of clean water in Jonggat using Ford Fulkerson algorithm and Dinic algorithm. Both Ford Fulkerson algorithm and Dinic algorithm are methods used to calculate the maximum flow in a network. Based on the results of research using Python software on the Ford Fulkerson algorithm, the maximum current is 133 liters/second, while using the Dinic algorithm, the maximum current is 133.49 liters/second. Meanwhile, the average water flow is delivered by PDAM is 95 liters/second. It means, it can be added the amount of flow in the clean water distribution pipe by the PDAM. It’s for facilitating the flow of water that reaches consumers with the addition of a flow that cannot exceed 133.49 liters/second. Keywords: Network flow, Maximum flow, Ford Fulkerson algorithm, Dinic algorithm